2010
DOI: 10.1039/b910469k
|View full text |Cite
|
Sign up to set email alerts
|

On the dissolution of non-metallic solid elements (sulfur, selenium, tellurium and phosphorus) in ionic liquids

Abstract: Ionic liquids are shown to be good solvents for elemental sulfur, selenium, phosphorus and tellurium, and can be designed to maximise the solubility of these elements. The presence of the [S(3)](*-) radical anion in diluted solutions of sulfur in some ionic liquids has been confirmed, and is the origin of their intense blue colour (cf. lapis lazuli).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
85
2
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(88 citation statements)
references
References 17 publications
0
85
2
1
Order By: Relevance
“…Boros et al. found that the dilute solution of tellurium in [P 6 6 6 14 ][decanoate] shows a purple color . Ding et al.…”
Section: Introductionmentioning
confidence: 99%
“…Boros et al. found that the dilute solution of tellurium in [P 6 6 6 14 ][decanoate] shows a purple color . Ding et al.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Among the many possible solvents in whicht he synthesis of phosphorus compounds from, for example, PCl 3 can be performed, ionic liquids (ILs) have remarkable potential. [15][16][17][18][19] Recently,R uck et al observed that in 1-hexyl-3-methylimidazoliumh alide ILs ([HMIm]Z;Z= Cl, Br,I )p hosphorust rihalides (PX 3 ;X= Cl, Br,I )c an readily undergo X-to-Zh alide exchange with the solvent, [20] which offersa ne fficientw ay of interconvertingt hese compounds. [2,5,14] Accordingly,s ignificants cientific attention has been devotedt oe xploring the possibility of combining the rich chemistryo fp hosphorus compounds and the versatility of IL solvents.…”
Section: Introductionmentioning
confidence: 99%
“…more recently reported detailed electrochemical studies of sulfur and sodium polysulfides in 1‐butyl‐3‐methylimidazolium dicyanamide . The solubility of chalcogens and phosphorus in a variety of ionic liquids comprising tosylate, bistriflimide, dithiocarbamate, and di‐ and trithiocarbonate anions was investigated by Seddon and co‐workers . The sulfur solubility in 1‐ethyl‐3‐methylimidazolium bistriflimide was also studied with the aim to electrodeposit metal sulfide films .…”
Section: Introductionmentioning
confidence: 99%